ANALYSIS OF ACTIVE PHASED ANTENNA ARRAY PARAMETERS FOR THE GURT RADIO TELESCOPE - P. L. Tokarsky (Radio Physics and Radio Astronomy, 2015)
The calculation technique results of numerical analysis of parameters of active phased antenna array (APAA) of the Giant Ukrainian Radio Telescope (GURT) of decameter and meter wavelengths which is being built now nearby Kharkiv at the area of S. Ya. Braude Radio Astronomy Observatory of the Institute of Radio Astronomy of the National Academy of Sciences of Ukraine are presented. The technique is based on the matrix theory of antenna arrays which combines an electromagnetic approach to analysis of radiators array with the methods of microwave multiport theory for the APAA feed network description. The results of numerical calculation of the APAA effective area and its gain, which in case of passive array is associated with its efficiency, are given and analyzed for a wide scan range within 10 to 80 MHz.